KADI ABDULCEBBAR'IN İMAMET ANLAYIŞI - GECEKUŞU, NİSA (Fırat Üniveristesi, 2012)
"Kadı Abdulcebbar'ın İmâmet Anlayışı" isimli çalışmamız giriş ve iki ana başlıktan oluşmaktadır. Giriş bölümünde Kadı Abdulcebbar'ın hayatı ile ilgili bilgilere yer verilmiştir. Birinci bölümde ise imâmet ile ilgili genel bir değerlendirme yapılmıştır. İkinci bölümde de Kadı Abdulcebbar'ın imâmet anlayışı ele alınmıştır. Kadı Abdulcebbar, imâmete ilişkin bağımsız bir duruşun sahibi olmuş ve imâmet düşüncesini ortaya koyarken Kur'an, Sünnet, dört halife ve tarihi deneyimleri referans olarak almıştır.

Our study named ?Qadı Abd al-Jabbar?s Imamate Understanding? consist of introduction and two main titles. In the introduction have been presented about the life of Abd al-Jabbar?. In the first chapter related with the imamate is evaluated. The second part discussed the concept of imamate Abd al-Jabbar?. Qadı Abd al-Jabbar?carved out an original political attitude; in defining his imamate doctrine, his founded his imamate doctrine on the Koran, the practices of the Prophet and the Rightly Guided Caliphs and historical experiences.
Qadı Abd al-Jabbar's imamate understanding
Keywords: Din